2020
DOI: 10.7150/jca.47175
|View full text |Cite
|
Sign up to set email alerts
|

Association between kidney function and the risk of cancer: Results from the China Health and Retirement longitudinal study (CHARLS)

Abstract: Objective: Increased cancer risk after dialysis or transplantation has been recognized, but studies of cancer in pre-dialysis chronic kidney disease (CKD) are extremely limited. Therefore, we aim to investigate the risk of cancer in individuals with reduced kidney function. Methods: This study was based on China Health and Retirement Longitudinal Study (CHARLS), a nationally representative population aged ≥ 45 years old. We included 11 508 (5364 male) individuals with measurement of serum creatinine and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
1
20
1
Order By: Relevance
“…To our knowledge, this is the first study to compare eGFRcr, eGFRcys and eGFRcr-cys for cancer risk. In contrast to studies that assessed the association between eGFRcr[ 3 , 5 , [7] , [8] , [9] , [10] , [11] , 27 ] or eGFRcr-cys [4] with cancer incidence and death, we have shown that eGFRcys 60–89 ml/min/1.73m 2 is associated with small but significant increases in cancer incidence, and a more pronounced association with cancer death.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, this is the first study to compare eGFRcr, eGFRcys and eGFRcr-cys for cancer risk. In contrast to studies that assessed the association between eGFRcr[ 3 , 5 , [7] , [8] , [9] , [10] , [11] , 27 ] or eGFRcr-cys [4] with cancer incidence and death, we have shown that eGFRcys 60–89 ml/min/1.73m 2 is associated with small but significant increases in cancer incidence, and a more pronounced association with cancer death.…”
Section: Discussioncontrasting
confidence: 99%
“…A more consistent association is observed between CKD and cancers of the urinary tract [ 1 , 3 , [7] , [8] , [9] , 29 ], which share common risk factors, such as the metabolic syndrome, smoking, prior nephrectomy, genetic conditions (such as tuberous sclerosis), occupational exposures and use of medications. Acute kidney injury (AKI) is known to contribute to CKD development [30] and is more likely to occur in those with CKD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations